Making Wawa : the genesis of Chinook jargon - Lang, George, 1945- (First nations languages., 2008)
"A two-edged sword of reconciliation and betrayal, Chinook Jargon (aka Wawa) arose at the interface of "Indian" and "White" societies in the Pacific Northwest. Wawa's sources lie first in the language of the Chinookans who lived along the lower Columbia River, but also with the Nootkans of the outer coast of Vancouver Island. With the arrival of the fur trade, the French of the engagés or voyageurs provided additional vocabulary and a set of viable cultural practices, a key element of which was marital bonding with Indian and métisse women. These women and their children were the first fluent speakers of Wawa.